Kesadaran Hukum Terhadap Larangan Pernikahan Dini - Ramadan, Sahrul (Jurnal El-Thawalib, 2022)
This research was motivated by public legal awareness of the prohibition of early marriage during the Covid-19 pandemic in Gunung Tua Jae Village, Panyabungan District. Early marriage is a marriage carried out by a spouse or one of the partners who are less than 19 years of age which has been regulated in Law no. 16 of 2019.The problem in this study is about the legal awareness of the community in Gunung Tua Jae Village, Panyabungan District against the prohibition of early marriage, many still do not know the importance of legal awareness about the age of marriage, marriage aims to meet basic human needs. These needs consist of emotional, biological, mutual need, and so on. In the village of Gunung Tua Jae, Panyabungan District, there are several people who have early marriages during this pandemic which resulted in quarrels in the household, miscarriages, and some even got divorced.This study aims to determine the legal awareness of the community towards the prohibition of early marriage during the Covid-19 pandemic in Gunung Tua Jae Village, Panyabungan District.This research was conducted directly in the field to obtain information and data as accurately as possible by using data collection techniques through interviews, and documentation. The objects in this study are religious leaders, community leaders, traditional leaders, NNB (Naposo Nauli Bulung).From the results of research conducted, the community in general only still knows the age of marriage is 16 years for women, the people of Gunung Tua Jae Village, Panyabungan District realize that early marriage is not wrong because what they understand is according to Imam Syafi'i's opinion that the daughter is an adult, meaning that he can take care of the household, he is allowed to marry. And the people of Gunung Tua Jae Village, Panyabungan District, even though their children have violated Islamic religion such as Pregnant Out of wedlock, they still register it at the KUA Panyabungan but after they are married according to custom.